Transparency in Neonatal Intensive Care - King, Nancy M. P. (The Hastings Center report, 1992)
Medical teams care for severely premature infants under conditions of emergency and uncertainty that make parental involvement very difficult. Parents can be invited into a decisional relationship with the team that enables them to assess more fully the meaning of their child's illness.